2006
DOI: 10.1111/j.1365-4632.2006.02936.x
|View full text |Cite
|
Sign up to set email alerts
|

Newborn with pseudohypoaldosteronism and miliaria rubra

Abstract: Pseudohypoaldosteronism type 1 is a rare autosomal recessive disorder with salt‐wasting, hyperkalemia, metabolic acidosis, and multiorgan aldosterone unresponsiveness, which results in an excessive loss of sodium chloride through urine, sweat and saliva, among other secretions. Inflammation of and around the damaged eccrine glands has been attributed to the deleterious effects of excessive eccrine gland salt exposure. Such a high concentration of salt in the sweat causes cutaneous lesions similar to those appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
9
0
4
Order By: Relevance
“…Akcakus et al [3] reported a patient with AR-PHA1 and cutaneous eruptions that were similar to those of our patient. They reported that the cutaneous eruptions might have been occurred due to obstruction of eccrine sweat glands through inflammation caused by excessive sodium excretion during hyponatremic crises (sweat sodium concentration, 138 mEq/l).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Akcakus et al [3] reported a patient with AR-PHA1 and cutaneous eruptions that were similar to those of our patient. They reported that the cutaneous eruptions might have been occurred due to obstruction of eccrine sweat glands through inflammation caused by excessive sodium excretion during hyponatremic crises (sweat sodium concentration, 138 mEq/l).…”
Section: Discussionsupporting
confidence: 86%
“…Sodium chloride is lost via the kidneys, resulting in a reduced sodium level and an elevated potassium level in the serum, and leading to life-threatening disturbances of water and acid-base concentrations. The excessive sodium loss has been considered to be caused by an unresponsiveness of the renal tubules to endogenous and exogenous mineralocorticoids [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition usually occurs at the elasticized openings of the diaper and at the superolateral abdomen, where the diaper tapes attach to the front panel of the diaper. 65,66 Scabies Frequent in certain socioeconomic areas. Scabies can involve the diaper region in infants.…”
Section: Prevention Of Diaper Dermatitismentioning
confidence: 99%
“…PHA is a rare heterogeneous syndrome of mineralocorticoid resistance classified as type 1, type 2 and type 3 [7,8]. PHA1 is a life-threatening salt-losing disease in neonates and infants.…”
Section: Discussionmentioning
confidence: 99%